IMPLEMENTASI PERGUB PROVINSI BALI NOMOR 80 TAHUN 2018 DI SMP DHARMA WIWEKA DENPASAR - I Wayan Sentana Putra; Rai Jaya Wangsa (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2022)
Dharma Wiweka Middle School Denpasar is a Junior High School located in Denpasar. As an educational institution, Dharma Wiweka Middle School Denpasar participated in implementing the Governor of Bali Province Regulation No. 80 of 2018 concerning the preservation of Balinese Script, Language and Literature and the implementation of the Balinese Language Month. This research method is descriptive qualitative with research results namely, the implementation of the Governor of Bali Province Regulation No. 80 of 2018 at SMP Dharma Wiweka Denpasar divided into four namely: A. Preservation of scripts by installing school name boards with a combination of Balinese script and Latin letters. Placement of Balinese script boards in each class as a means of student learning. B. Language preservation is carried out by using Balinese every Thursday, full moon and tilem which are carried out at the end of collective prayers, and the use of Balinese posters. C. Literature preservation is carried out with the availability of Balinese language literacy books and the availability of tembang extracurriculars. D. Balinese Language Month is held with various competitions, both participated by students and by teachers. Among them are Balinese poetry competitions, Balinese script writing competitions, and Masatua competitions.Keywords: Dharma Wiweka Junior High School , Implementation, Governor Regulation